Blood pressure control in the general and high risk populations, longitudinal trends. (14th October 2021) - Bruthans, J; Mayer, O; Cifkova, R
Abstract: Introduction: Despite better control of high blood pressure (BP) in the general as well as high cardiovascular (CV) risk populations as a factor contributing to the decrease in CV mortality since 1990, the targets set by the guidelines may not have been reached. Purpose: We analysed longitudinal trends in BP control in the general and high risk populations, to assess implementation of guidelines and to identify subpopulations with still unsatisfactory BP control. Methods: Analysis of seven independent surveys of the general population (Czech MONICA and post-MONICA studies, 1985–2017) and five independent surveys of patients with stable manifest coronary heart disease (CHD) 1995–2017 (Czech samples of the EUROASPIRE I-V surveys). Results: A total of 15 000 persons (Czech MONICA) and 2 098 patients (Czech EUROASPIRE) were investigated. In the 1985–2017 period, mean systolic BP decreased in the general population (MONICA) from 134 to 128 mmHg (p<0.001) and diastolic BP from 84 to 82.5 mmHg (p<0.01), hypertensive levels of BP (>140/90mmHg) were found in 45% in 1995 but only in 27.5% in 2017, and the prevalence of uncontrolled severe hypertension (BP>180/110 mmHg) decreased from 3 to 1%. The proportion of properly controlled hypertension increased from 13.2 to 53% (p<0.0001). In the 1995–2017 surveys of the high-risk population (EUROASPIRE) systolic BP decreased from 144.1 to 135.5 mmHg (p<0.001), diastolic BP from 87.5to 83.5mmHg (p<0.01), higher than recommended BP (>140/90mmHg, >140/85mmHg in diabetics) was found in 66.2% in 1995, still present as much as in 54.4% in 2017. Proportion of patients with very high BP (BP>180/110 mmHg) decreased from 18.4 to 1% only. Drugs with a potentially antihypertensive effect were used in 79.9 and 95.3% of patients in 1995 and 2017, respectively (p<0.0001). Population BP levels ceased to decline since 2000/01 survey, in the CHD population since the 2012/13 survey. This is obviously due to considerable increase in prevalence of obesity, and an increasing prevalence of diabetes, both in the general and high-risk populations. The more intensive medical high BP treatment seems to have a beneficial effect on hypertension control, even more in the general than in the high risk population. Conclusions: The recent trend in BP levels, both in the general and high-risk populations, are far from satisfactory, with the main causative factor suggested to be the increasing prevalence of obesity and diabetes. While there has been progress in hypertension control, more in the general nad limited in high-risk population, truly effective BP control may be illusory without comprehensive CV risk factor control. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Agency for Medical Research, Ministry of Health of the Czech Republic